Determinants of staff job satisfaction of caregivers in two nursing homes in Pennsylvania - Degenholtz Howard; Castle Nicholas G; Rosen Jules (BMC, 2006)
Abstract Background Job satisfaction is important for nursing home staff and nursing home management, as it is associated with absenteeism, turnover, and quality of care. However, we know little about factors associated with job satisfaction and dissatisfaction for nursing home workers. Methods In this investigation, we use data from 251 caregivers (i.e., Registered Nurses, Licensed Practical Nurses, and Nurse Aides) to examine: job satisfaction scores of these caregivers and what characteristics of these caregivers are associated with job satisfaction. The data were collected from two nursing homes over a two and a half year period with five waves of data collection at six-month intervals. The Job Description Index was used to collect job satisfaction data. Results We find that, overall nursing home caregivers are satisfied with the work and coworkers, but are less satisfied with promotional opportunities, superiors, and compensation. From exploratory factor analysis three domains represented the data, pay, management, and work. Nurse aides appear particularly sensitive to the work domain. Of significance, we also find that caregivers who perceived the quality of care to be high have higher job satisfaction on all three domains than those who do not. Conclusion These results may be important in guiding caregiver retention initiatives in nursing homes. The finding for quality may be especially important, and indicates that nursing homes that improve their quality may have a positive impact on job satisfaction of staff, and thereby reduce their turnover rates.